Imprensa e política no Piauí na primeira metade do período monárquico (Ágora Journal, 2020)
The purpose of the article is to analyze the circumstances of the creation of the press in Piauí, during the Regency period and the beginning of the Second Reign. Oeiras, the capital and main political center of the Province of Piauí, was located in the hinterland, far from the coast and marked by economic dynamics and specific material and cultural conditions that reflected the way of doing politics in force in the province. In the period, Piauí was governed by Barão da Parnaíba, who imposed a fierce vigilance on everyone who stood against him, making it difficult for a free press to appear, which would give visibility to oppositional ideas. Understanding the particularities of the creation of the press in the Province of Piauí between the years 1832, the year in which the first newspaper in the province was created, and the year 1845, when the first oppositions newspaper was launched in the Province of Piauí, is the questions that we propose to analyze.